Начертательная геометрия: учебное пособие для вузов - Буркова С. П. Светлана Петровна; Винокурова Г. Ф. Галина Федоровна; Долотова Р. Г. Раиса Григорьевна; Степанов Б. Л. Борис Леонидович (Томск, Изд-во ТПУ, 2011)
Параллельный текст на англ. яз.